Indirect detection of respiratory viruses responsible for respiratory disease in sheep - Franco, Mariane Ferreira; Gaeta, Natália Carrillo; Alemán, Mario Augusto Reyes; Nogueira, Adriana Hellmeister Campos; Pituco, Ediviges Maristela; Balaro, Mario Felipe Alvarez; Gregory, Lilian (Medicina Veterinária, 2020)
Respiratory disease in sheep is an important disease in sheep flocks, in which viruses are categorized as primary etiological agents. It is responsible for elevated economic losses in sheep production and new data about its occurrence and the etiological agents are necessary to understand its situation in Brazilian flocks. This research aimed to detect antibodies against Bovine Viral Diarrhea Virus, Bovine Herpesvirus type 1, Bovine Respiratory Syncytial Virus (BRSV) and Bovine Parainfluenza type 3 (bPI-3) virus in healthy and pneumonic sheep in relation to clinical signs of respiratory disease. Ninety-nine male and female sheep from the states of São Paulo (SP) and Rio de Janeiro (RJ) were enrolled in this study. They were classified as healthy and pneumonic using physical examination. Serum samples were obtained, and they were used to determine the presence of antibodies against respiratory viruses using serum neutralization test. The association between the microorganisms, clinical status, and clinical signs of respiratory disease in sheep was evaluated. Antibodies against Bovine Parainfluenza type 3 virus were mainly detected (52.5%), followed by Bovine Respiratory Syncytial Virus (48.5%). Data analysis did not reveal any association between the presence of antibodies and clinical signs of respiratory disease in sheep. Respiratory disease is an important issue in sheep production in which different bacterial and viral etiologic agents may be involved in its development. BRSV and bPI-3 are circulating in sheep flocks from São Paulo and Rio de Janeiro.